2015
DOI: 10.1016/j.rpor.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Could preoperative short-course radiotherapy be the treatment of choice for localized advanced rectal carcinoma?

Abstract: Short-course preoperative radiotherapy (RT) is widely used in northern Europe for locally advanced resectable rectal cancer, but its role in the era of advanced imaging techniques is uncertain. Here, we reviewed articles and abstracts on SCRT published from 1974 through 2013 with the goal of identifying patients who might be best suited for short-course RT. We included relevant articles comparing surgery with or without preoperative radiation published before and after the advent of total mesorectal excision. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Treatment approach to rectal cancer has greatly evolved over the past years. In locally advanced rectal cancer (LARC), neoadjuvant chemoradiotherapy (CRT) followed by surgical resection with total mesorectal excision is the current standard treatment approach [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment approach to rectal cancer has greatly evolved over the past years. In locally advanced rectal cancer (LARC), neoadjuvant chemoradiotherapy (CRT) followed by surgical resection with total mesorectal excision is the current standard treatment approach [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of several studies is to determine the types of polyps which have the malignancy potential. This is a very significant problem among pathologists, oncologists and other clinicians [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study indicated that if preoperative radiotherapy is to be effective, then the biologically equivalent dose should be at least 20 Gy [ 22 ]. Furthermore, another study reported that different doses of preoperative radiotherapy (≥30 Gy) could have anticancer biological effects [ 23 ].…”
Section: Discussionmentioning
confidence: 99%